Two-phase natural circulation and flow boiling with seawater - Franken, Daniel (Kansas State University, 2019)
Two-phase natural circulation experiments were performed with artificial seawater as a working fluid. The experimental work performed in this investigation is focused on understanding the role of dissolved salts in the water on steady-state two-phase natural circulation flow rate characteristics. Experiments were performed measuring mass flow rates on a natural circulation loop with three process fluids, artificial seawater, tap water, and deionized water. The flow characteristics of each fluid were captured at the same heat flux and pressure condition to measure differences in mass flow rate and hydrodynamic conditions. The time-averaged mass flow rates under a quasi-steady state condition were found to be very similar under the same heat flux conditions for each fluid. Artificial seawater showed to be more stable compared to the other two fluids at higher heat flux. Instrumentation measurements recorded at approximately a 2-second interval showed that mass flow oscillations were significantly higher in the cases of the tap water and deionized water. The use of a high-speed camera showed that the bubble departure diameters were much smaller for the artificial seawater case compared to the other cases. The smaller departure diameters were partly attributed to the increase in local wettability caused by the scale formation during boiling. Another explanation to the smaller departure diameters is the local increase in salt concentration around the bubble, which increased the local boiling point and reduced bubble growth time. The use of a visually transparent riser section revealed that the artificial seawater inhibited bubble coalescence and resulted in a bubbly flow regime for the range of heat fluxes tested. The observations in characteristic flow changes explained the reduced pressure drop across the test section when artificial seawater was used.
Keywords: Natural circulation; Seawater; Two-phase; Flow; Boiling